International human rights documents - Ghandhi, P. R., 1951- (Oxford : Oxford University Press, 2006)
This work contains all the relevant regional and international instruments, and covers the essential United Nations resolutions and international conventions.
Previous ed.: 2004.
Includes index.
Cover title: Blackstone's international human rights documents.
Includes web resources.
Keywords: Human rights; Mensenrechten